Growth and biomass allocation in seedlings of rain-forest trees in New Caledonia: monodominants vs. subordinates and episodic vs. continuous regenerators. (19th January 2017) - Read, Jennifer; McCoy, Stephane; Jaffré, Tanguy; Sanson, Gordon; Logan, Murray
Abstract: Some species-rich secondary forests in New Caledonia have a monodominant canopy. Here we investigate growth and biomass allocation traits that might explain single-species' dominance of these post-disturbance stands, and their later decline in the absence of large-scale disturbance. Seedlings of 20 rain-forest trees were grown in two light treatments in a nursery house. In the sun treatment, monodominants grew faster (56.7 ± 1.4 mg g −1 wk −1 ) than subordinates (40.2 ± 2.6 mg g −1 wk −1 ). However, some episodically regenerating (ER) subordinates had high growth rates similar to those of monodominants. In the shade treatment, monodominants and subordinates had similar growth rates (33.7 ± 2.6 and 34.0 ± 1.9 mg g −1 wk −1 respectively). Notably, monodominants in both sun and shade treatments had lower root mass fraction (0.29 ± 0.02 and 0.27 ± 0.02 g g −1 respectively) than subordinates (0.39 ± 0.02 and 0.37 ± 0.02 g g −1 ). Fast growth in sunny conditions is probably imperative for these relatively shade-intolerant ER monodominants. In field conditions, high shoot mass fraction combined with efficient root performance may facilitate faster growth in monodominants competing with other ER species in sunlit sites. Slower growth in shade may contribute to loss of dominance over time in undisturbed forests.